The rethinking thesis within the context of state-economy nexus: a political theory of knowledge - T. Salami, Adebayo (Faculty of Administrative Science and Policy Studies, 2024)
Human/political life is fundamentally linked to nature. Nature consequently has a kind of influence on the organization of human/political life for both survival and sustenance. As man attempts to wrestle with nature, he invented the state. What exactly the state is has however, become a subject of disputation particularly from the perspective of its assigned roles, duties and functions in relation to ensuring human/political life survival and sustenance. The emerging disputes in relation to the primary and secondary existence of the state are being influenced by equally related quadrupling developments in which human/political life is embedded and further being permanently determined. This is the inescapable reality of human/political life. Within the context of the foregoing therefore, the paper/article seeks the amplification of state rethinking thesis within the broad and specific ideas in relation to the emerging interrogation organized around important and relevant themes in relation to the knowledge of the subject matter. Relying on qualitative data sources and placed within the usefulness of the concept of economic management to enable the amplification of the state rethinking thesis, the paper/article sets as its central objective the development of a political theory of knowledge founded on carefully formulated intellectual foundation stones relevant to the amplification of the embedded thesis.